2021
DOI: 10.3389/fnsys.2021.785366
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Predictive Postural Control Against Floor Tilting in Rats

Abstract: Humans and animals learn the internal model of bodies and environments from their experience and stabilize posture against disturbances based on the predicted future states according to the internal model. We evaluated the mechanism of predictive control during standing, by using rats to construct a novel experimental system and comparing their behaviors with a mathematical model. In the experiments, rats (n = 6) that were standing upright using their hindlimbs were given a sensory input of light, after a cert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…As previously discussed 15 , the basic mechanics of postural fluctuations due to floor-tilting disturbances are common between bipedal rats and humans. Therefore, the kinematic and neural strategies adopted by the rats in this study can be extrapolated from human studies.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…As previously discussed 15 , the basic mechanics of postural fluctuations due to floor-tilting disturbances are common between bipedal rats and humans. Therefore, the kinematic and neural strategies adopted by the rats in this study can be extrapolated from human studies.…”
Section: Discussionmentioning
confidence: 85%
“…However, as most of these studies used behavioral tasks that could be performed under head-fixed conditions, such as blinking, saccades, and licking, the detailed mechanisms of predictive postural control remain unclear. Under these circumstances, an experimental system for floor tilting, which has been widely utilized to evaluate postural stability 14 , has recently been developed for rats 15 . Biomechanical fluctuations in upright-standing rats due to the disturbance generally agreed with those in humans, and comparisons between the experimental data and a simulation suggested that the rats acquired predictive muscle outputs at the hind limb joints based on the time difference between the conditioning stimulus and disturbance.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that body segments of rats during quiet bipedal standing are comparable but flexed compared to those of humans which are nearly aligned (Funato et al, 2017). In the study that explored bipedal rats' postural responses to the backward rotation of the floor, the researchers showed that the postural responses were generally common between humans and rats but found the bending of the trunk in rats as a response to the floor rotation, which is not commonly observed in humans (Konosu et al, 2021). They suggested that this might be due to the mass and length of the trunk accounting for a greater proportion of the rat's whole body compared to humans, as well as the aforementioned alignment differences.…”
Section: Discussionmentioning
confidence: 99%
“…We developed a postural perturbation task in freely moving mice, modeled after those used in human studies (Horak et al, 1989;Kolb et al, 2002;Welch and Ting, 2014) and a recent rat study (Konosu et al, 2021), in which a dynamic platform is used to give reproducible perturbations.…”
Section: Predictive Postural Control Taskmentioning
confidence: 99%
See 1 more Smart Citation